Literature Review: Determinants of Knowledge, Attitude, Social Support, and Nutritional Awareness on Premarital Screening Compliance among Prospective Brides in Indonesia - Soraya, Andi Bella Gading; Situmorang, Anita; Arum Sari, Ayu; Rita Wadun, Aplonia; Natalia Mau, Deliana; Obed, Dinawati; Susanti, Dwi; Puspowati, Erwin; Purnamasari Azis, Ira; Nazdia, Nazdia (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Premarital screening is an essential step in preventing reproductive health risks and improving preconception readiness among prospective brides. However, compliance with premarital screening in Indonesia remains low. This study aims to identify the determinants of knowledge, attitude, social support, and nutritional awareness influencing premarital screening compliance among prospective brides in Indonesia. A narrative synthesis method was applied to relevant national and international studies published between 2018 and 2024 in midwifery and public health journals. The findings revealed that good knowledge and positive attitudes, along with social support from partners, families, and healthcare providers, play an important role in improving compliance with premarital screening. Moreover, nutritional awareness related to anemia prevention and folic acid intake contributes to preconception readiness. Digital-based education has been proven effective in enhancing understanding and participation among prospective brides. In conclusion, compliance with premarital screening is influenced by cognitive, social, and nutritional factors. Therefore, integrating nutrition education and digital approaches into premarital programs is essential to strengthen reproductive health readiness.